Δ9-Tetrahydrocannabinol elicited 22-kHz ultrasonic vocalization changes after air puff stimulus through CB1 receptor in adult rats. (14th May 2019) - Myose, Takayuki; Shirakawa, Atsunori; Irie, Keiichi; Yamashita, Yuta; Nakano, Takafumi; Takase, Yumi; Matsuo, Koichi; Satho, Tomomitsu; Tuchihashi, Ryota; Kinjo, Junei; Tanaka, Hiroyuki; Morimoto, Satoshi; et al.
Highlights: THC does not affect 22- or 50-kHz USVs in the absence of stimulus in adult rats. THC increases the number of 22-kHz USVs after air puff stimulus in adult rats. SR141716 inhibits THC-induced 22-kHz USVs after air puff stimulus. Abstract: Δ 9 -Tetrahydrocannabinol (THC) is known to have various pharmacological effects mediated through activation of cannabinoid CB1 and CB2 receptors in rodents. In adult rats, 22- and 50-kHz ultrasonic vocalizations (USVs) serve as an effective communication system and as indicators of negative and positive states, respectively. The present study was performed to determine whether THC affects USVs in adult rats, and to determine the roles of cannabinoid receptors in these effects. THC (1, 3 mg/kg) was administered intraperitoneally to adult male Wistar rats 60 min before measurement of USVs. The CB1 antagonist, SR141716 (3, 6 mg/kg), or CB2 antagonist, AM630 (1, 10 mg/kg), was administered intraperitoneally 10 min before THC. USVs were measured during a 5-minute period without air puff stimulus or with air puff stimulus. THC did not affect 22- or 50-kHz USVs without air puff stimulus. On the other hand, THC significantly increased the number of 22-kHz USVs, but not 50-kHz USVs, after air puff stimulus. Moreover, SR141716 at 6 mg/kg, but not AM630 at either dose, inhibited the increase in number of 22-kHz USVs induced by THC after air puff stimulus. These results suggest that THC induced changes in sensitivity to aversive air puff stimuli through CB1 receptors, and as a result increased emission of 22-kHz USVs in rats.